PENINGKATAN KOMPETENSI MANAJEMEN SUMBER DAYA MANUSIA UNTUK PENGUATAN KINERJA KOPERASI DI KOTA SEMARANG - Andini, Rita; Nurdiyanto, Ahmad Dwi; Mohklas, Mohklas; Hidayati, Salma Aprilia; Pangesti, Vivi Setyo (ICON Publisher, 2025)
This community service activity aims to improve human resource (HR) management competency to strengthen the performance of cooperatives in Semarang City. The main problems faced by cooperatives are low managerial skills, a lack of HR development planning, and the absence of an objective performance evaluation system. The activity was implemented through a participatory approach that included interactive training, field mentoring, and applied evaluation. The program targets cooperative administrators and staff directly involved in organizational management. The results of the activity showed a 78% increase in participants' managerial competency, a 65% increase in work planning capabilities, and a 23% increase in operational efficiency. In addition, the Semarang City Cooperative HR Communication Forum was established as a form of sustainability for the activity. This training successfully shifted the paradigm of cooperative HR management from merely administrative to a strategic, competency-based system. This community service activity made a real contribution to increasing cooperative competitiveness, strengthening a collaborative culture, and establishing a HR development model that can be replicated in other regions.